Diagnostic laparoscopy in a twelve year old girl with right iliac fossa pain: A life changing diagnosis of complete androgen insensitivity syndrome - Meshkat, Babak (Elsevier, 2014)
INTRODUCTION: Right iliac fossa (RIF) pain is one of the most common presenting complaints faced by general surgeons in the emergency department. Correct diagnosis and appropriate surgical intervention can often pose a challenge. PRESENTATION OF CASE: A 12-year-old girl presented to the emergency department with a four day history of initially central acute abdominal pain, now localised in the RIF. During laparoscopy, the following findings were made: macroscopically dilated appendix, right and left gonads at the internal opening of the inguinal canal, empty pelvis with a rudimentary uterus on the right side. No evidence of fallopian tubes or connection of uterus to the vagina and broad based, non-inflamed Meckel's diverticulum. An incidental diagnosis of complete androgen insensitivity syndrome was made. DISCUSSION: Androgen insensitivity syndrome (AIS) is a disorder of hormone resistance characterised by a female phenotype in an individual with an XY karyotype and testes producing age-appropriate normal concentrations of androgens. CONCLUSION: This case report highlights the advantage of laparoscopy as a diagnostic and treatment tool in a twelve year old girl with multiple intra-abdominal findings. While the ultimate diagnosis responsible for her symptom of RIF pain was acute appendicitis, the additional diagnosis of CAIS and incidental Meckel's would have otherwise likely gone undetected.